2007
DOI: 10.1677/joe-07-0303
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoid receptor and CCAAT/enhancer-binding protein α in the feed-forward induction of 11β-hydroxysteroid dehydrogenase type 1 expression by cortisol in human amnion fibroblasts

Abstract: The amount of cortisol available to its receptors is increased by the pre-receptor enzyme 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1) which converts cortisone to cortisol. We examined the molecular mechanisms of the feedback effect of cortisol on 11b-HSD1 mRNA expression in human amnion fibroblasts. Our data showed that cortisol-induced 11b-HSD1 mRNA expression dose dependently in amnion fibroblasts, which could be completely blocked both by the mRNA transcription inhibitor 5,6-dichlorobenzimidazole rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 35 publications
2
54
3
Order By: Relevance
“…Two C/EBP sites close to the transcription start and highly conserved between human, rat, and mouse (244,775) are critical for basal and regulated expression (775), either alone or in concert with other transcription factors including GR (789).…”
Section: A Gene Structure and Controlmentioning
confidence: 99%
“…Two C/EBP sites close to the transcription start and highly conserved between human, rat, and mouse (244,775) are critical for basal and regulated expression (775), either alone or in concert with other transcription factors including GR (789).…”
Section: A Gene Structure and Controlmentioning
confidence: 99%
“…GR-mediated transcriptional activation is modulated by phosphorylation [29]. GRs are highly expressed in decidua, chorion, amnion, stromal fibroblasts, vascular smooth muscle cells and endothelial cells of human term placentas, with moderate expression in cytotrophoblasts and negligible expression in syncytiotrophoblast [30][31][32][33][34]. Because the significance of glucocorticoids to the early mammalian embryo is clear and glucocorticoid action within the cell is regulated by GR, we investigated GR expression during the course of rat embryogenesis until day 12 of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids up-regulate 11b-HSD1 expression in a number of tissues or cell types (Tomlinson et al, 2004) and we demonstrated that glucocorticoids induced 11b-HSD1 expression in fibroblast cells and trophoblast cells derived from human fetal membranes at concentrations easily achieved at the end of pregnancy (Sun and Myatt 2003;Li et al 2006;Yang et al 2007). We found this induction of 11β-HSD1 expression by glucocorticoids was a GR mediated on-going transcriptional process and verified the CCAAT consensus sequence and a GRE existing within the promoter region responsible for the induction of 11β-HSD1 by glucocorticoids (Yang et al, 2007).…”
Section: Cortisol In the Fetal Circulationmentioning
confidence: 64%